Health system response to large scale migration: the case of Emilia-Romagna region. (30th September 2020) - Quargnolo, M; Mammana, L; Gherardi, G; Bodini, C; Damosto, D; Florescu, C; Fantini, M P
Abstract: Background: In Italy, recent changes in migration flows posed complex public health challenges. The Emilia-Romagna region (ERR) was one of the first regions to adopt specific policies addressing the health of newly arrived asylum seekers. In our study, we analysed the regional health system response comparing it to the regional and national guidelines, in order to assess its strengths and its critical areas. Methods: In 2019, we conducted a survey among the referents of the regional clinics that provide healthcare to asylum seekers, in order to learn about local policies, challenges and best practices. A questionnaire with 35 closed and 11 open questions was administered and analysed through descriptive statistical analysis and text analysis. Results: Regional policies showed good responsiveness and Local Health Authorities (LHAs) adhered to the guidelines. A special permit was introduced to grant asylum seekers access to healthcare, which also allowed integration of health data into the regional health information system. However, data integration was done in only 2 clinics out of 14. Instances of discretion in issuing the special permit were reported, due to ambiguity in the rules and inadequate training of office workers. Policies and LHAs protocols focused greatly on the arrival phase and on Communicable Diseases (CDs) surveillance. Other areas - such as protection of vulnerable groups, health promotion, NCDs - were prioritized in the national guidelines, but unevenly considered throughout the region, also due to lack of resources. Some clinics responded autonomously to these gaps with local resources. Conclusions: The ERR health response to the influx of asylum seekers was rapid but incomplete. Interventions focused more on CDs surveillance than on responding to asylum seekers' health needs in terms of quality, access and equity. Areas to be strengthened include protection of vulnerable groups, health promotion and NCDs, together with coordination and long-term planning. Key messages: The Emilia-Romagna region health response to the influx of asylum seekers reflects an emergency approach focused on communicable diseases, while NCDs and health promotion are relatively neglected. The health system in Emilia-Romagna needs to be strengthened in its capacity to respond to asylum seekers' health needs. Health policies and practices should be planned to ensure equity and quality.